Buccal Permeation of Polysaccharide High Molecular Weight Compounds: Effect of Chemical Permeation Enhancers - Adriana Fantini; Luca Giulio; Andrea Delledonne; Silvia Pescina; Cristina Sissa; Sara Nicoli; Patrizia Santi; Cristina Padula (Pharmaceutics, 2022)
The greatest achievement in the advanced drug delivery field should be the optimization of non-invasive formulations for the delivery of high molecular weight compounds. Peptides, proteins, and other macromolecules can have poor membrane permeation, principally due to their large molecular weight. The aim of this work was to explore the possibility of administering fluorescently labeled dextrans (molecular weight 4–150 kDa) across the buccal mucosa. Permeation experiments across pig esophageal mucosa were carried out using fatty acids and bile salts as penetration enhancers. The data obtained show that it is possible to increase or promote the mucosa permeation of high molecular weight dextrans by using caprylic acid or sodium taurocholate as the chemical enhancers. With these enhancers, dextrans with molecular weight of 70 and 150 kDa, that in passive conditions did not permeate, could cross the mucosa in detectable amounts. FD-70 and FD-150 showed comparable permeability values, despite the molecular weight difference. The results obtained in the present work suggest that the buccal administration of high molecular weight compounds is feasible.